2011
DOI: 10.5897/ajpp10.355
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of green tea polyphenols in treatment of pharyngitis in human subjects

Abstract: Tea from Camellia sinensis (L.) Kuntze has long been used in herb medicine and recognized to possess anti-inflammative effects. The aim of the current study was to evaluate the therapeutic effects of green tea polyphenols in treatment of pharyngitis in human subjects. The clinical study was carried out as a randomized, double-blind, parallel-group comparative trial. It was found that the integral scores of all the observed individual clinical signs and symptoms were decreased significantly from pre-treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Pharyngitis is one of the common diseases characterized by the typical signs of inflammation signs: rubor, tumor, calor and dolor. In our clinical trial, green tea polyphenols were found as an effective phytochemical in the treatment of pharyngitis (Wang et al, 2011). Furthermore, in the present study, CEGTE was shown to be practically non-toxic in the bacterial and animal experiments.…”
Section: Discussionmentioning
confidence: 60%
“…Pharyngitis is one of the common diseases characterized by the typical signs of inflammation signs: rubor, tumor, calor and dolor. In our clinical trial, green tea polyphenols were found as an effective phytochemical in the treatment of pharyngitis (Wang et al, 2011). Furthermore, in the present study, CEGTE was shown to be practically non-toxic in the bacterial and animal experiments.…”
Section: Discussionmentioning
confidence: 60%